A solvent-free, one-step synthesis of sulfonic acid group-functionalized mesoporous organosilica with ultra-high acid concentrations and excellent catalytic activities. Issue 5 (7th February 2018) - Wu, Qin; Liu, Fujian; Yi, Xianfeng; Zou, Yongcun; Jiang, Lilong
Abstract : A green, solvent-free and rapid synthesis of highly sulfonic acid group-functionalized mesoporous organosilica, which act as efficient solid acid in biomass conversion and fine chemicals synthesis. Abstract : We demonstrate herein a novel solvent-free technique for the synthesis of sulfonic acid group-functionalized mesoporous organosilica, which was achieved from the self-assembly of a block copolymer template using mercaptopropyltrimethoxysilane (MPTS) and tetramethoxysilane (TMOS) under melting conditions without using additional solvents and subsequent condensation at high temperature (up to 140 °C). The resultant samples were designated as SMS- x s, where x stands for molar ratio of MPTS/(MPTS + TMOS). SMS- x s have relatively large BET surface areas, highly cross-linked frameworks, and abundant and uniform mesopores with wormhole-like characteristics. Interestingly, MPTS could be used as the solo precursor to prepare mesoporous organosilica (SMS-1.0), which had controllable acidity and an ultra-high concentration of sulfur (5.51 mmol g −1, the highest acid density to date), which was even higher than those of commercial Amberlyst 15 (4.7 mmol g −1 ), HS-JLU-20-0.8 (4.61 mmol g −1 ) and sulfonated carbon (CH0.30 O0.33 S0.16, 4.90 mmol g −1 ). These structural characteristics give SMS- x s excellent activities and good reusability in biomass conversions and fine chemicals synthesis, which are much better than various solid acids, such as Amberlyst 15, H-form USY zeolite, and sulfonic acid group-functionalized ordered mesoporous silica.